Connected Stores, Connected Brands, Connected Consumers, Connected Goods: On Business Model Ecosystems in Internet of Packaging - Lydekaityte, Justina; Tambo, Torben (Nordic and Baltic Journal of Information & Communications Technologies, 2020)
This paper investigates and discusses roles, initiatives, and potentials for the business model ecosystem to enter business model innovation triggered by digital wireless technologies and capabilities of the Internet of Packaging-enabled smart interactive packaging. This paper develops an overview of the Internet of Packaging technology, wireless digital capabilities, business model innovation, and business model ecosystem in connection to the investigated phenomenon. In this paper, the digital transformation from passive to network-connected enhanced packaging is considered as an accelerator for business model innovation that creates and delivers the value proposition to a wide-ranging business model ecosystem including internal and external participants. Therefore, the governance of the overall business model ecosystem should efficiently reinforce each separate business model, as well as ensure safe and reliable data mobility in the IoP digital infrastructure regarding unique secure digital identifiers.